2008
DOI: 10.1111/j.1365-4632.2008.03473.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of autoantibodies to BP180 correlate with disease activity in patients with bullous pemphigoid

Abstract: BP180 antibody titers showed a closer correlation than indirect immunofluorescence titers to disease activity. The titer of BP180 antibody may be a useful tool for the evaluation of disease activity and for the assessment of the effectiveness of treatments in BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 11 publications
4
53
0
2
Order By: Relevance
“…All but seven patients (4.89%) with mild diseases required systemic therapy. Specific data about the number of patients on different systemic and/or topical treatments was not available for two reports (17,24). All patients clinically improved with the treatment(s) they received (12,16,17,(19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…All but seven patients (4.89%) with mild diseases required systemic therapy. Specific data about the number of patients on different systemic and/or topical treatments was not available for two reports (17,24). All patients clinically improved with the treatment(s) they received (12,16,17,(19)(20)(21)(22)(23)(24).…”
Section: Resultsmentioning
confidence: 92%
“…Nine reports, which contained data on 143 patients (12,16,17,(19)(20)(21)(22)(23)(24), published between August 1977 and February 2009, were included in this analysis. However, 51 studies were excluded because they lacked the inclusion criteria set out below.…”
Section: Materials Atsld Methodsmentioning
confidence: 99%
“…In particular, anti-BP180 antibody reactivity is closely associated with BP, as it is detectable with absolute accuracy in almost all patients with BP [5][6][7]. Moreover, serum levels of anti-BP180 antibody correlate with disease activity [8]. Bullous pemphigoid has been associated with various renal lesions, and many studies have found that the severity of skin lesions parallels that of kidney disease.…”
Section: Discussionmentioning
confidence: 98%
“…Les marqueurs d'activité de la PB sont cliniques (nombre de nouvelles bulles par jour avec si possible une moyenne sur 3 jours) et biologiques avec le taux d'Ac anti-BP180 (ELISA BP180-NC16A) en cours de traitement et non l'immunofluorescence indirecte [28,29]. Les facteurs prédictifs de rechute dans l'année après l'arrêt du traitement sont le taux élevé d'Ac anti-BP180 et la positivité de l'immunofluorescence directe (IFD) à l'arrêt du traitement [30].…”
Section: éVolution Pronosticunclassified